2016
DOI: 10.1093/cid/ciw030
|View full text |Cite
|
Sign up to set email alerts
|

Recent Thymus Emigrant CD4+ T Cells Predict HIV Disease Progression in Patients With Perinatally Acquired HIV

Abstract: CD4+RTE% predicts disease progression and may reflect history of disease in HIV-positive patients and adolescents. They are easy to measure in the clinical setting and may be helpful markers in guiding treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…showed that INRs had a lower naïve CD4 + T‐cell increase and a lower percentage of CD4 + RTE than immunological responders and healthy controls, indicating that reduced thymic output may be a major mechanism of incomplete immune reconstitution . In accordance, it has been reported that thymic function, measured by the sj/β‐TREC ratio or CD4 + RTE%, can predict HIV‐1 disease progression in HIV‐1‐infected adults and adolescents with perinatally acquired HIV‐1 . These studies indicate that reduced thymic output may play an important role in the incomplete immune reconstitution of HIV‐1‐infected individuals.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionsupporting
confidence: 63%
See 1 more Smart Citation
“…showed that INRs had a lower naïve CD4 + T‐cell increase and a lower percentage of CD4 + RTE than immunological responders and healthy controls, indicating that reduced thymic output may be a major mechanism of incomplete immune reconstitution . In accordance, it has been reported that thymic function, measured by the sj/β‐TREC ratio or CD4 + RTE%, can predict HIV‐1 disease progression in HIV‐1‐infected adults and adolescents with perinatally acquired HIV‐1 . These studies indicate that reduced thymic output may play an important role in the incomplete immune reconstitution of HIV‐1‐infected individuals.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionsupporting
confidence: 63%
“…50 In accordance, it has been reported that thymic function, measured by the sj/ -TREC ratio or CD4 + RTE%, can predict HIV-1 disease progression in HIV-1-infected adults and adolescents with perinatally acquired HIV-1. 51,52 These studies indicate that reduced thymic output may play an important role in the incomplete immune reconstitution of HIV-1infected individuals. Conversely, Cobos Jiménez et al found in HIV-1infected ART-experienced 45-year-old adults with detectable viremia (<50 copies/ml) for at least 1 year, the percentage of CD31 + CD4 + cells and Sj-TREC content in PBMCs are much higher than those in healthy controls.…”
Section: Thymus and Naïve Cellsmentioning
confidence: 95%
“…Moreover, some studies have described an increased infectivity of CD4 T SCM 58,69 and T RTE by HIV (or SIV in the case of the Rhesus Macaque) in progressors 57 . A preserved T RTE compartment is also associated with higher CD4 nadir 66 . That HIV could gain an evolutionary advantage by undermining CD4 T SCM and T RTE function suggests their importance in the control of viral replication.…”
Section: Discussionmentioning
confidence: 96%
“…However, CDR3 diversity in T SCM is reduced during aging and, in the absence of cognate epitopes, T SCM persistence depends heavily on homeostatic proliferation (mediated through IL-7, IL-15, or IL-21) and the differentiation of scarce T RTE 11 . An increase in IL-7 levels was further correlated to the loss of naive 64 and CD4 T RTE cells 65 , which are both predictive of poor HIV prognosis [64][65][66] . Furthermore, co-infection with HCV presents an additional burden that contributes to the loss of T RTE 67 .…”
Section: Discussionmentioning
confidence: 97%
“…These findings are probably due to an enhanced need for the recruitment of RTE to regenerate mature naïve T cells in patients with major homeostatic disturbances compared with those in more stable conditions in which cell loss and cell production appeared more balanced. 20,21 The children with no evidence of immunosuppression also showed higher central and effector memory CD4 + T cell counts but lower percentage levels of these subsets compared with the children with severe immunosuppression. This discrepancy might be accounted for by the fact that children with better clinical conditions had higher total CD4 + T cell counts.…”
Section: Discussionmentioning
confidence: 98%